Comparative growth and mortality of cultured Lion's Paw scallops (Nodipecten subnodosus) from Gulf of California and Pacific populations and their reciprocal transplants. (15th March 2013) - Koch, Volker; Rengstorf, Anna; Taylor, Marc; Mazón‐Suástegui, José M.; Sinsel, Francisco; Wolff, Matthias
Abstract This study focused on the comparison of growth and mortality of Lion's Paw scallops Nodipecten subnodosus from Gulf of California and Pacific populations and their reciprocal transplants, cultured in suspended module and bottom culture in Baja California Sur, Mexico. Environmental parameters were monitored to determine site‐specific differences and were correlated with scallops' population‐specific responses. Significant differences in growth were found between sites, populations and grow‐out methods. Growth performance of scallops originating from the Pacific population was lower and uniform between Pacific and Gulf culture sites, whereas Gulf scallops cultured at the Pacific site grew better. Growth and survival was higher in suspended than bottom culture, mainly due to depth‐associated differences in food and oxygen supply. Increasing temperatures and decreasing food and oxygen during summer months resulted in depressed growth and elevated mortality. At the Pacific site, this was partially compensated by considerably higher food availability. Gulf scallops resisted high diurnal temperature changes at San Buto significantly better than Pacific scallops. They also survived generally better than the Pacific population, independent of site and grow‐out method, indicating physiological adaptations to high temperatures and low food availability in their habitat. Consequently, the Gulf population appears to be more feasible for aquaculture operations in coastal lagoons with stressful conditions.